Editorial Vol.6 (Journal of Tourism and Himalayan Adventures, 2024)
Journal of Nepal Mountain Academy is purely an official publication. As part of NMA’s regular academic exercises, it has planned to publish an academic journal annually focusing on mountain science, the adventures and mountaineering. It has aimed at promoting research in mountain science, socio-culture and tourism activities among the researchers, college and university professors, graduate and undergraduate students, personnel in administrative positions involved in research ventures, and academicians/ professionals immersed in the tourism sectors. As obvious from the title of the journal, mainly research articles from the field of tourism, adventure, mountain science, and mountaineering are preferred for publication.The articles published in this journal in all its issues are from mountain science, environment, culture and general tourism area. The articles were assigned for peer review to the professors and practitioners in their respective fields, amendments were recommended followed by editing corrections ensured before they were processed for publication.However, the editorial team does not bear any responsibility for any incongruences in contents and patterns presented in the articles as they are purely the products of their authors, and hence, the authors are subject to ethical interrogations in the circumstances that are marked to violate ethical parameters applicable in the field of academics and research.The articles have been arranged in alphabetical order of the authors' name. Researchers and readers are welcome for their any kind of scholarly inquiries and suggestions.Thank You.Prof. Dr. Sunil AdhikaryChief Editor